Réactions sociales face aux comportements déviants : problèmes de théorie et de méthode [1962] - John I. Kitsuse (Genre, Sexualité et Société)
In dedicating this article to social reactions to homosexuality, the author chose to focus on behavior deemed deviant through characterization and social treatment. He emphasizes the idea that "deviance" is not an intrinsic quality of an individual but comes from social definition of his behavior, an idea that forms the heart of labeling theory.